Myocardial Recovery in Peripartum Cardiomyopathy After Hyperprolactinemia Treatment on BIVAD. Issue 1 (January 2017) - Wiedemann, Dominik; Schlöglhofer, Thomas; Riebandt, Julia; Neuner, Markus; Tschernko, Edda; Schima, Heinrich; Zimpfer, Daniel
Abstract : Peripartum cardiomyopathy (PPCMP) requiring mechanical circulatory support is rare; however, it is a life-threatening disease with recovery rates poorer than expected. Herein, we describe a case of successful recovery of a patient with PPCMP. Implantation of a biventricular ventricular assist device was performed; additionally, the patient's hyperprolactinemia was treated with cabergoline, resulting in a fast complete restoration of ventricular function.